In & out of Amsterdam : travels in conceptual art, 1960-1976 - Cherix, Christophe; Museum of Modern Art (New York, N.Y.) (New York : Museum of Modern Art, 2009)
- Director's Foreword / Glenn D. Lowry##- Preface / Christophe Cherix##- Greetings from Amsterdam / Christophe Cherix##- Art & Project: The Early Years / Rini Dippel##- OP Losse Schroeven: Tentative Connections / Christian Rattemeyer##- Between L.A. and Amsterdam: Thank You, Mr. Duchamp / Phillip Van den Bossche##- Bas Jan Ader##- Stanley Brouwn##- Hanne Darboven##- Jan Dibbets##- Ger Van Elk##- Gilbert & George##- Sol Lewin##- Charlotte Posenenske##- Allen Ruppersberg##- Lawrence Weiner##- Checklist of Art & Project/Depot VBVR Gift##- On the Passage of a Few Persons Through a Rather Brief Unity of Time: Amsterdam, 1960-1976.
"Published in conjunction with the exhibition ... organized by Christophe Cherix, Curator in the Department of Prints and Illustrated Books, [and held] at The Museum of Modern Art, New York, July 19-October 5, 2009"--T.p. verso.
Includes bibliographical references (p. 166-167) and index.
boek